ANALISIS EKSPOR KOMODITAS PERTANIAN PANGAN DI JAWA TIMUR - Suprapti, Anis (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2014)
This research is kind of descriptive qualitative research with the title â€œthe analysis offood agriculture export commodity in east javaâ€. The purpose of this research is to know how the development of contribution influence food agriculture toward food agriculture export commodity in east java. The instrument of this research is analysis export developing, analysis export contributing, and to know the output effect of food agriculture production, exchange rate rupiah to dollar and inflation phase using analysis bifilar regression through experiment F and experiment T that use experiment data panel fixed effect. From the analysis result, it could be simplified that the developing export commodity food agriculture result the increasingly commodity of green bean, cassava, and mango. The biggest contribution of the commodity is rice, corn, and cassava during five year. From the aggression analysis partially stated that output production of food agriculture exchange rate rupiah to dollar, inflation phase, bring the positive effect toward export value of food agriculture in east java.Â